Inaction as a Legal Fact in Civil Law (on the Example of the Republic of Belarus) - Šafalovič, Ana (Teisė, 2019)
Unlike other legal sciences, the science of civil law did not produce any meaningful theory of inaction as a legal fact. The purpose of this article is to fill in this blank space. As a result of research, the author exposes certain features of the legal fact of inaction in the branch of civil law and draws conclusions regarding it – as a special type of act, in a number of cases having signs of action.